Realization of Ultraflat Plastic Film Using Dressed-Photon-Phonon-Assisted Selective Etching of Nanoscale Structures. (2nd February 2015) - Yatsui, Takashi; Nomura, Wataru; Ohtsu, Motoichi
Abstract : We compared dressed-photon-phonon (DPP) etching to conventional photochemical etching and, using a numerical analysis of topographic images of the resultant etched polymethyl methacrylate (PMMA) substrate, we determined that the DPP etching resulted in the selective etching of smaller scale structures in comparison with the conventional photochemical etching. We investigated the wavelength dependence of the PMMA substrate etching using an O2 gas. As the dissociation energy of O2 is 5.12 eV, we applied a continuous-wave (CW) He-Cd laser (λ = 325 nm, 3.81 eV) for the DPP etching and a 5th-harmonic Nd:YAG laser (λ = 213 nm, 5.82 eV) for the conventional photochemical etching. From the obtained atomic force microscope images, we confirmed a reduction in surface roughness, R a, in both cases. However, based on calculations involving the standard deviation of the height difference function, we confirmed that the conventional photochemical etching method etched the larger scale structures only, while the DPP etching process selectively etched the smaller scale features.